A mean variance king? Creation and resolution of uncertainty under the employment report's reign - Nikolaus Hautsch; Dieter E. Hess (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper delineates the simultaneous impact of non-anticipated information on first and second moments of the intraday price process by including appropriate variables accounting for the news flow into both the mean and the variance function. This allows us to differentiate between the consistent price reaction to surprising news and traders? uncertainty about the precise price impact of this information. Analyzing the US employment report, we find that headline information is almost instantaneously incorporated into T-bond futures prices. Nevertheless, large surprises create considerable uncertainty, in particular ?bad? news. In contrast, if surprises in related headlines cross-validate each other, less room for differences of opinion is left, and hence volatility is decreased.
Keywords: G14; E44; 330; Information processing; trading process; volatility; macroeconomic announcements; Treasury bond futures; high-frequency data; Börsenkurs; Volatilität; Schatzpapier; Zinstermingeschäft; Maßzahl; Information; Arbeitsmarktstatistik; Informationsverbreitung; Ankündigungseffekt; Schätzung; USA